Analysis of Improvement in the Energy Efficiency of Office Buildings Based on Energy Performance Certificates - Raimondas Bliūdžius; Karolis Banionis; Edmundas Monstvilas; Rosita Norvaišienė; Dinarr Adilova; Aleksejs Prozuments; Anatolijs Borodinecs (Buildings)
The article presents an analysis of changes in energy efficiency of new office buildings designed and constructed during the implementation period of the Energy Performance of Buildings Directive (2014–2024). Common criteria on energy efficiency were collected from Energy Performance Certificates (EPCs) and processed. The changes in final and primary energy for space heating, cooling and hot water production of certified office buildings were determined, and the improvements in buildings, their energy systems and energy sources were analysed. It was determined that buildings of Class C, designed between 2006 and 2017, showed an average thermal energy consumption for heating of 61, for cooling of 13 and for hot water production of 30 kWh/(m2·year), while buildings of Class A++, designed after 2020, consumed, respectively, 6, 9 and 17 kWh/(m2·year). The main reasons for these changes in energy consumption are the significant improvement of thermal insulation, increase of renewable energy in the heat supplied by district heating, the use of heat pumps for cooling, more efficient hot water boilers and optimized and insulated distribution pipelines. Even better results were hindered by the increased area of glazing, insufficient use of solar protection, users’ preference for buildings of complex shape, and technically complicated electricity production. The results revealed that EPCs are an appropriate database for the analysis of changes in energy efficiency of buildings and for setting tasks for further improvement.